Short-term amino acid infusion improves protein balance in critically ill patients - Liebau, Felix (Crit Care, 2015)
INTRODUCTION: Evidence behind the recommendations for protein feeding during critical illness is weak. Mechanistic studies are needed to elucidate the effects of amino acid and/or protein supplementation on protein metabolism before larger clinical trials with higher levels of protein feeding are initiated. METHODS: We studied the effects of parenteral amino acid supplementation (equivalent to 1 g/kg/day) over the course of 3 hours on whole-body protein turnover in critically ill patients in the intensive care unit (ICU) during the first week after admission. Patients were studied at baseline during ongoing nutrition and during extra amino acid supplementation. If the patient was still in the ICU 2 to 4 days later, these measurements were repeated. Protein kinetics were measured using continuous stable isotope-labeled phenylalanine and tyrosine infusions. RESULTS: Thirteen patients were studied on the first study occasion only, and seven were studied twice. Parenteral amino acid supplementation significantly improved protein balance on both occasions, from a median of −4 to +7 μmol phenylalanine/kg/hr (P =0.001) on the first study day and from a median of 0 to +12 μmol phenylalanine/kg/hr (P =0.018) on the second study day. The more positive protein balance was attributed to an increased protein synthesis rate, which reached statistical significance during the first measurement (from 58 to 65 μmol phenylalanine/kg/hr; n =13; P =0.007), but not during the second measurement (from 58 to 69 μmol phenylalanine/kg/hr; n =7; P =0.09). Amino acid oxidation rates, estimated by phenylalanine hydroxylation, did not increase during the 3-hour amino acid infusion. A positive correlation (r =0.80; P <0.0001) was observed between total amino acids and/or protein given to the patient and whole-body protein balance. CONCLUSION: Extra parenteral amino acids infused over a 3-hour period improved whole-body protein balance and did not increase amino acid oxidation rates in critically ill patients during the early phase (first week) of critical illness. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13054-015-0844-6) contains supplementary material, which is available to authorized users.